A Comparison of Serum Thyroxine [T4(D)], RT3U Ratio and T4-RT3 Index with Radioiodine Uptake in the Triiodothyronine Suppression Test - Höschl, R.; Gimlette, T. M. D. (Nuklearmedizin - NuclearMedicine, 1972)
A total of 132 triiodothyronine suppression tests were performed using 100 μg of T3 for 7 days. Radioiodine uptake at four hours, serum thyroxine [T4(D)], T3 binding coefficient [RT3U ratio] and free thyroxine index [T4-RT3 index] were estimated before and after a course of triiodothyronine.T4(D) decreased significantly in only 38.4% of T3 suppression tests assessed as positive by the decrease in radioiodine uptake; it did not change or increased significantly in 84.7% of tests negative by radioiodine uptake.RT3U ratio showed little change in all groups. The changes in T4-RT3 index were similar to those of T4(D).The correlation of changes in T4(D) with 4 hour radioiodine uptake is poor (r = 0.34).Agreement between changes in radioiodine uptake and T4(D) was observed only in 54% of tests; between changes in uptake and T4-RT3 index in 69.4%.Estimation of serum thyroxine or free thyroxine index in the T3 suppression test cannot substitute for the radioiodine uptake for reasons which are discussed.